PENGARUH KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI ANGKRINGAN ROMUSHA NGANJUK - Santika, Nabilla (Universitas Nusantara PGRI Kediri, 2022)
The background of the research is to find out how the behavior of consumer purchasing decisions is influenced by service quality, price and location at Angkringan Romusha Nganjuk. This study applies a quantitative approach and causality techniques. The population used is all consumers who have made a purchase at Angkringan Romusha Nganjuk with an unknown number, using 40 respondents as the sample. By using incidental sampling sampling technique. The data collection tool uses a questionnaire. The data analysis technique used is multiple linear regression analysis with the help of SPSS. The results showed that the quality of service, price, and location on purchasing decisions at Angkringan Romusha Nganjuk. The results show that partially service quality, price and location have a significant effect on purchasing decisions, and service quality, price, and location simultaneously or together have a significant influence on purchasing decisions at Angkringan Romusha Nganjuk.